Evapotranspiration and water use efficiency of hybrid napier + berseem intercropping system under organic and inorganic nutrition - J. B. SINGH; PRADEEP BEHARI; R. K. AGRAWAL; SUNIL KUMAR (Journal of Agrometeorology, 2012)
An experiment was conducted during rabi seasons of 2009 and 2010 to assess the crop evapotranspiration of hybrid napier+berseem intercropping system using four weighing lysimeters under organic and inorganic nutrition. The estimated water use efficiency of the system shows that the maximum water use efficiency coincides with the second cutting and it was higher in case of organic as compared to inorganic nutrition. Cut wise water use efficiency of the intercropping system as a function of evapotranspiration under both situations showed a significant (P < 0.05) negative linear relationship. The crop coefficient value at each cutting interval has crossed the unit value (>1) and the highest value coincides with the first cutting in organic as well as inorganic situation.